2021
DOI: 10.1093/jrs/feaa131
|View full text |Cite
|
Sign up to set email alerts
|

The Capability ‘To Be Secure’: Media Coverage of African Asylum Seekers During Covid-19 in Israel

Abstract: The health and economic consequences of Covid-19 have not affected the different groups in society equally, particularly the weakest communities, chief among them asylum seekers who have been hit the hardest. This study focuses on the Israeli media’s role during this crisis, and whether they have advocated or hindered African asylum seekers capability ‘to be secure’. This capability is the most important in the capabilities approach, as it advocates not only quality of life but also life itself. The study reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
(59 reference statements)
2
10
0
Order By: Relevance
“…Second, we showed that the media outlets in our sample scarcely referred to refugees, when reported on Covid-19. Refugees constitute one of the most vulnerable population groups, facing disproportionate hardships when it comes to access to healthcare (Shomron, 2021). Yet, the epidemiological developments or other health aspects related to local populations seem to overshadow the situation of refugees, whose position seemed to be further marginalised by the low media salience.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, we showed that the media outlets in our sample scarcely referred to refugees, when reported on Covid-19. Refugees constitute one of the most vulnerable population groups, facing disproportionate hardships when it comes to access to healthcare (Shomron, 2021). Yet, the epidemiological developments or other health aspects related to local populations seem to overshadow the situation of refugees, whose position seemed to be further marginalised by the low media salience.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Meanwhile, when an infectious disease emerges, not everyone is affected the same way, and Covid-19 is not an exception (Edmonds & Flahault, 2021). Social inequality and exclusion have been exacerbated, while the most marginalised and vulnerable populations in society have faced disproportionate hardships when it comes to access to healthcare (Shomron, 2021).…”
Section: Introduction: Conceptual and Methodological Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…Geographers are starting to explore emerging bordering processes by investigating which spatial (and at times racialised) imaginaries COVID‐era maps convey, as well as how these are incorporated in popular mappings and with what implications in terms of bordering practices (Pase et al., 2021). Research is also addressing how media coverage of asylum seekers is reinforcing or subverting borders in healthcare (Shomron, 2021), although more extensive studies on the visual dimensions of the pandemic are needed. While before COVID visuals of migrant crossings dominated newspapers and often spread xenophobic political attitudes, the pandemic's intensified injustices in amplifying forced immobility – illustrated by protracted refugee detention and encampment – present one of many avenues for visually engaging with COVID‐era borderings, as recently done by contributions in borderlands studies (Brunet‐Jailly & Carpenter, 2020) and in line with growing interest in the intersections between visuality and migration (Nikielska‐Sekula & Amandine, 2021).…”
Section: Bordering Visuality and Covid‐19mentioning
confidence: 99%
“…In Nigeria, vaccine development received moderate media attention, with concise stories and the predominance of official sources [Asogwa, 2021]. A number of other studies have focused on media coverage of the pandemic on specific topics, such as immigration [Shomron, 2021], the economy [Atri, Kouki & imen Gallali, 2021], tourism [H. Chen, Huang & Li, 2020], childhood [Katz & Cohen, 2021], old age [Morgan, Wiles, Williams & Gott, 2021] and health workers [Lynch, Evans, Ice & Costa, 2021]. The present study extends this approach by analyzing the full coverage of the COVID-19 pandemic, without restricting it to a specific theme, over a considerably longer period (most studies focus on the initial months of the pandemic, while we analyzed a full year), and in a cross-national perspective.…”
Section: When Science and Journalism Meetmentioning
confidence: 99%